2019
DOI: 10.5194/amt-12-691-2019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the particle emission from a ship operating at sea using an unmanned aerial vehicle

Abstract: Abstract. This research demonstrates the use of an unmanned aerial vehicle (UAV) to characterize the gaseous (CO2) and particle (10–500 nm) emissions of a ship at sea. The field study was part of the research voyage “The Great Barrier Reef as a significant source of climatically relevant aerosol particles” on board the RV Investigator around the Australian Great Barrier Reef. Measurements of the RV Investigator exhaust plume were carried out while the ship was operating at sea, at a steady engine load of 30 %.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Furthermore, the addition of gas and/or particulate matter (PM) sensors on the drone makes it possible to obtain air quality data as well. For example, drones equipped with atmospheric sensors Atmosphere 2021, 12, 376 2 of 16 have been applied to measure the emissions of pollutant sources, such as ship exhaust or open burning [6][7][8]. Aside from these emission point source investigations, the vertical profile of gases and PM concentrations in the atmospheric boundary layer have also been examined via drones [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of gas and/or particulate matter (PM) sensors on the drone makes it possible to obtain air quality data as well. For example, drones equipped with atmospheric sensors Atmosphere 2021, 12, 376 2 of 16 have been applied to measure the emissions of pollutant sources, such as ship exhaust or open burning [6][7][8]. Aside from these emission point source investigations, the vertical profile of gases and PM concentrations in the atmospheric boundary layer have also been examined via drones [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Villa et al. (2019) measured the total EIPN and found an average value of ∼7.6 ± 1.4 × 10 15 no. kg −1 fuel in open waters, while Sinha et al.…”
Section: Introductionmentioning
confidence: 99%
“…kg −1 fuel (Jonsson et al, 2011;Juwono et al, 2013;Lack et al, 2009Lack et al, , 2011Sinha et al, 2003;Westerlund et al, 2015). Villa et al (2019) measured the total EIPN and found an average value of ∼7.6 ± 1.4 × 10 15 no. kg −1 fuel in open waters, while Sinha et al (2003) reported a value of up to 6.2 ± 0.6 × 10 16 no.…”
mentioning
confidence: 99%
“…Ship emissions can be divided into land-based Yang et al, 2016), airborne-based Aliabadi et al, 2016), marine-based (Cappa et al, 2014), satellite-based (Ding et al, 2018), and unmanned aerial vehicle (UAV)-based (Villa et al, 2019) measurements according to different platforms. Land-based measurements provide continuous observation but are greatly affected by wind speed, wind direction, and the distance between the ship and equipment.…”
Section: Introductionmentioning
confidence: 99%